Granuloma Annulare, Autoimmune Thyroiditis, and Lichen Sclerosus in a Woman: Randomness or Significant Association? - Mariele De Paola; Anastasia Batsikosta; Luca Feci; Mattia Benedetti; Roberta Bilenchi (Case Reports in Dermatological Medicine)
We report a 60-year-old Caucasian female with a 2-year history of diffused granuloma annulare (GA), who presented for the simultaneous occurrence of genital lichen sclerosus (LS) and autoimmune thyroiditis (AT). In our opinion this combination is not just coincidental but may share similar immunopathological mechanisms.